Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (University of Minnesota Press, 2009)
"A nuanced critique of how the World Bank encourages gender norms through its policies, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations.By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world's largest and most influential development institution. Looking concurrently at economic and gender policy, Bedford connects reform of markets to reform of masculinities, loan agreements for export promotion to pamphlets for indigenous adolescents advising daily genital bathing, and attempts to strengthen institutions after the Washington Consensus to efforts to promote loving couplehood in response to economic crisis. In doing so, she reveals the shifting relationships between development and sexuality and the ways in which gender policy impacts debates about the future of neoliberalism.Providing a multilayered account of how gender-aware policies are conceived and implemented by the World Bank, Developing Partnerships demonstrates as well how institutional practices shape development."– Site de l'éditeur.
Keywords: LGBTQIA2+; approches et analyses; care; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie

Les années - Ernaux, Annie (Gallimard, 2009)
Annie Ernaux s'efforce ici de retrouver les différents visages et la vie de sa mère, morte le 7 avril 1986, au terme d'une maladie qui avait détruit sa mémoire et son intégrité intellectuelle et physique. Elle, si active, si ouverte au monde. Quête de l'existence d'une femme, ouvrière, puis commerçante anxieuse de «tenir son rang» et d'apprendre. Mise au jour, aussi, de l'évolution et de l'ambivalence des sentiments d'une fille pour sa mère : amour, haine, tendresse, culpabilité, et, pour finir, attachement viscéral à la vieille femme diminuée.
Section: 241 pages ; 21 cm
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; care; classisme; cours; discipline; europe; famille; france; inégalités; lit301N; littérature; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; systèmes d'oppressions; thématiques; écriture des femmes*

Qu'est-ce que le care?: souci des autres, sensibilité, responsabilité - Molinier, Pascale; Laugier, Sandra; Paperman, Patricia (Éditions Payot & Rivages, 2009)
"Apporter une réponse concrète aux besoins des autres, telle est, aujourd'hui, la définition du care, ce concept qui ne relève pas, comme on l'a longtemps cru, du seul souci des autres ni d'une préoccupation spécifiquement féminine, mais d'une question politique cruciale recoupant l'expérience quotidienne de la plupart d'entre nous. Première synthèse sur cette notion d'une très grande ampleur après les travaux fondateurs de Carol Gilligan dans les années 1980 puis de Joan Tronto dans les années 1990, ce livre concerne aussi bien le domaine du travail que ceux du genre, de l'éthique et de la santé."
Section: 302 pages ; 17 cm.
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail du care